A Comparison of Swarm Intelligence Algorithms Exploiting a Novel Neighbour Generation Technique - (:unkn) unknown (Springer Science and Business Media Deutschland GmbH, 2021)
This study aims at introducing a new perspective on a widely known Capacitated Vehicle Routing Problem (CVRP). Migrating birds optimization (MBO) algorithm is applied to solve the CVRP for the first time, to the best of our knowledge. Besides, a novel multi directional neighbourhood search heuristic is presented. MBO is compared with the state-of-the-art algorithms that have already shown a good performance on CVRP on a number of benchmark instances and a real data set. Experimental results indicate that the MBO is 3.89% better than the other algorithms on obtaining shorter routes. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.